An A‐Site Mixed‐Ammonium Solid Solution Perovskite Series of [(NH2NH3)x(CH3NH3)1−x][Mn(HCOO)3] (x=1.00–0.67). Issue 38 (4th August 2015) - Chen, Sa; Shang, Ran; Wang, Bing‐Wu; Wang, Zhe‐Ming; Gao, Song
Abstract The A‐site mixed‐ammonium solid solutions of metal–organic perovskites [(NH2NH3)x(CH3NH3)1−x][Mn(HCOO)3] (x=1.00–0.67) exhibit para‐ to ferroelectric diffuse phase transitions with lowered transition temperatures from x=1.00 to 0.67. These properties are due to the decreased framework distortion and polarization in their low temperature ferroelectric phases caused by the increased CH3NH3+ concentration.